Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Square terhadap Aktivitas Belajar Dan Hasil Belajar Matatematika Siswa Kelas XI IPA SMAN 1 Bonjol Kabupaten Pasaman - HARRY MAGDA HAYATULLAH (Jurnal Edukasi dan Penelitian Matematika, 2019)
Learning outcomes are the results achieved by students or someone after learning activities. Therefore we need an appropriate learning process in improving learning outcomes. But in reality the learning process carried out at SMAN 1 Bonjol is not success to ascend  the result of learning mathematic. The process of learning mathematics at SMAN 1 Bonjol is still focus on the teacher. In addition, student learning activities are still not visible in the learning process. One solution to ascend learning activities and result is to apply Think Pair Square (TPSq) cooperative learning models. The direction of this study was to describe student learning activities during the TPSq type cooperative learning model, and see whether students' mathematics learning outcomes by applying TPSq type cooperative learning models were better than student result of learning with conventional learning of students of class XI IPA SMAN 1 Bonjol. The instrument used was a learning achievement test. Proof of research hypothesis with the Mann Whitney test. From the data analysis, for the level of α = 0.05, it can be  concluded that the activities of students studied with the TPSq model experienced fluctuations at every meeting, and the result of learning mathematics students in class XI IPA SMAN 1 Bonjol taught by applying the cooperative learning model Think Pair Square type were better than with conventional learning.Keyword---Cooperative Learning, Student Activities, Result of Learning Mathematicals, Think Pair Square.